Penguatan Peran Guru Dalam Implementasi Kurikulum Merdeka Belajar - Siti Sakinahria Binti Dahlan (JURNAL PENCAKAR (Pendidikan Pancasila dan Kewarganegaraan), 2026)
The essence of Merdeka Belajar (Freedom to Learn) lies in the independence of both teachers and students in the learning process. The modern educational paradigm asserts that teachers should be respected for their knowledge, competence, and especially their character. Therefore, they are worthy of being called teachers, individuals who are trusted and emulated.This study aims to explain the concept and meaning of Merdeka Belajar as well as the role of teachers within it. The method used in this research is a literature review. The results of the study are as follows: (1) There are four main guidelines in Merdeka Belajar: school-based national standard examinations, minimum competency assessment and character evaluation, simplification of lesson plans (RPP), and the zoning system for student admissions. (2) The meaning of Merdeka Belajar includes freedom of thought, freedom to innovate, independence in creative learning, and the freedom to experience joy in learning. (3) The role of teachers in Merdeka Belajar includes being facilitators of independent learning, innovative and creative educators, individuals with strong teaching character, and drivers of educational transformation. Based on these findings, the study shows that understanding the importance of Merdeka Belajar and the role of teachers within it encourages both teachers and students to become more independent, more innovative and creative in their thinking, and happier in the learning process.